Academic librarianship today - Gilman, Todd (Rowman & Littlefield, 2017)
Intended for use by librarians and students in LIS programs, Academic Librarianship Today is the most current, comprehensive overview of the field available today. The book begins with Gilman's introduction, an overview that briefly synthesizes the contents of the contributors' chapters by highlighting major themes.